Operative Confidence Among U.S General Surgery Residents. Issue 4 (April 2023) - Elkbuli, Adel; Ehrlich, Haley; Gargano, Toria; Newsome, Kevin; Liu, Huazhi; McKenney, Mark; Ang, Darwin
Background: General surgery residents (GSRs) must develop operative autonomy skills to practice independently after graduation. We aim to investigate perceived confidence and operative autonomy of GSR physicians in order to identify and address influential factors. Methods: A 28-question anonymous online survey was distributed to 23 United States general surgery residency programs. Multivariable logistic regression was used for calculating the adjusted odds ratio (aOR) for binary outcomes. Significance was defined as P-values ≤ .05 or 95% confidence intervals (CIs) >1 or <1. Results: There were 120/558 (21.5%) GSR respondents. General surgery residents with >200 overall operative case volume reported significantly higher confidence with minor cases (P = .05) and major cases (P = .02). General surgery residents that performed both minor and major surgeries reported higher confidence with minor cases at 85.7% compared to GSRs that performed mostly minor surgeries (64.7%) and mostly major surgeries (62.5%). General surgery residents who performed >50 minor surgeries during their PGY 1 and 2 were less confident with major cases than GSRs who performed <50 minor surgeries (aOR: 19.98, 95% CI: 1.26, 318). General surgery residents from community teaching hospitals reported higher confidence with major and minor cases than GSRs from university teaching hospitals and combined programs. Conclusion: Increased case volume, predominant case type, early surgical experience during PGY 1 and 2 years, and training at community teaching hospitals were identified as the most important factors that positively influence perception of operative confidence and autonomy among GSRs. These may have important implications in the development of future surgeons.